Multimodality analysis of Jokowi's Social Exchange Theory and Political Marketing to Ma'ruf Amin's infidelity at the 2019 Presidential Election Contestation - Agustinus Rustanta; Evvy Silalahi (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2020)
In the constellation of the 2019 presidential election, there is something very interesting. Prabowo's camp quickly announced his vice-presidential candidate but Jokowi did not immediately announce his chosen vice-presidential candidate. Even until the last moment, Jokowi let the issue of the vice-presidential candidate rolling in the community. Unexpectedly, Jokowi chose a man who was never included in consideration of public. Jokowi's choice also made several names with the initials M as stated himself that his chosen vice-presidential candidate was M. Surprisingly, he announced that his chosen vice-presidential candidate was Ma'ruf Amin, a senior cleric and Chairman of the MUI (Majelis Ulama Indonesia). The issue of Ma'ruf Amin's selection in this study focuses on social exchange theory from Richard Emerson and the concept of political marketing from Jennifer Lees, especially the MOP (Market Oriented Product) model with a qualitative multimodality approach. Data were analysed using a visual text analysis to dig deeper into Jokowi's non-verbal meaning by deciding to choose Ma'ruf Amin as a vice-presidential candidate. The data were photos of the nomination of the presidential and vice-presidential. The findings of this study are that the election of Ma'ruf Amin is the most appropriate and accurate choice to defeat Prabowo. By choosing Ma'ruf Amin, Jokowi won before competing against Prabowo. Ma'ruf is a symbol, means, and source of Jokowi's victory